Illuminating friendship as ethical virtue (philia) in Saint Maximus the Confessor and Aristotle - Negraru, Nicoleta (Diakrisis, 2020)
This study has pursued a microcosmic perspective of the Maximian ethics, the doctrine of love, and friendship and the role of love in the manifestation of virtuosity through ongoing ethical transformation. In Saint Maximus’ view, the internal integrity of the spiritual microcosm is closely connected with the integrity of the interrelations in the new form of politeia. One of the most beautiful ethical themes of this interpretation is the theme of friendship (philia), highlighted by Saint Maximus to demonstrate the integrity of love and, implicitly, of ethical virtue, as an expression of cosmic reconciliation. I have illustrated the interpretation of one of the spiritual models of ethical virtue, namely the spiritual friendship (philia), seen as that state whereby virtue, and also vice, can be surprised directly and can be involved in virtue education.